MUATAN SOSIAL, POLITIK, DAN BUDAYA KANDHA DAN SINDHENAN TARI BEDHAYA SEMANG DALAM NASKAH SERAT KANDHA BEDHAYA SRIMPI - Adji, Fransisca Tjandrasih (Patra Widya: Seri Penerbitan Penelitian Sejarah dan Budaya., 2019)
Bedhaya dance is a classical dance that is very old and is the original art of kingdoms in Java. As a dance genre, bedhaya is placed as one of the most important arts in the Yogyakarta Palace. In the bedhaya dance, the important element to make it easier to know the story is in the kandha and the sindhenan. Kandha and sindhenan become mediations for the audience to understand the context of the bedhaya dance. as far as the author is concerned, the kandha and the sindhenan of bedhaya dance has never been discussed by observers of bedhaya dance. The things that are widely discussed are the choreography and symbolic meaning of the bedhaya dance. The Serat Kandha Bedhaya Srimpi is one of manuscript of the KHP Widya Budaya, Ngayogyakarta Hadiningrat Palace (with the text code W.7-B 24). That is the only manuscript that appeared in the period of Hamengku Buwana V which contained the bedhaya dance and which can still be read. In this manuscript there are kandha and the sindhenan of the Bedhaya Semang dance, which are different from the kandha and the sindhenan of the Bedhaya Semang dance in several other texts. To see the difference, an intertextual approach is used. The difference between the kandha and the sindhenan of Bedhaya Semang dance relates to the ideology of Hamengku Buwana V. Thus, through the kandha and the sindhenan of the Bedhaya Semang dance in the text W.7-B 24, the ideology of Hamengku Buwana V can be understood.